Xerostomia Therapy Due to Ionized Radiation Using Preconditioned Bone Marrow-Derived Mesenchymal Stem Cells - Sri Wigati Mardi Mulyani, - (Eur J Dent, 2019)
Objectives The aim of this study was to describe the process of regeneration of damaged salivary glands due to ionizing radiations by bone marrow mesenchymal stem cells (BM-MSCs) transplantation that have been given hypoxic preconditioning with 1% O2 concentration. Materials and Methods Stem cell culture was performed under normoxic (O2: 21%)and hypoxic conditions by incubating the cells for 48 hours in a low oxygen tension chamber consisting of 95% N2, 5% CO2, and 1% O2. Thirty male Wistar rats were divided into four groups: two groups of control and two groups of treatment. A single dose of 15 Gy radiation was provided to the ventral region of the neck in all treatment groups, damaging the salivary glands. BM-MSCs transplantation was performed in the treatment groups for normoxia and hypoxia 24-hour postradiation. Statistical Analysis Statistical analysis was done using normality test, followed by MANOVA test (p < 0.05). Results There was a significant difference in the expression of binding SDF1-CXCR4, Bcl-2 (p < 0.05) and also the activity of the enzyme α-amylase in all groups of hypoxia. Conclusion BM-MSCs transplantation with hypoxic precondition increases the expression of binding SDF1-CXCR4, Bcl-2 that contributes to cell migration, cell survival, and cell differentiation.